1989
DOI: 10.1135/cccc19890091
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration of silica sols

Abstract: Ultrafiltration of three laboratory made silica and two commercial silica sols was studied using Amicon YC membrane in a 200 ml capacity batch-cell. The effect of silica particle size, stirring conditions, pressure, pH and silica contents on ultrafiltration was investigated. The results obtained indicate that the smaller particles have, disregarding the stirring conditions, lower filtration flux. The differences observed in filtration flux are more pronounced in the conditions without stirring. The obtained va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…It appears that dependence of specific resistance on bulk feed concentration and applied pressure is due to the nature &the deposit and particle size distribution in suspension. Previous studies have suggested that specific resistance of silica gel depends on physiochemical properties of bulk solution and operating conditions [9][10][11][12]. The specific resistance of this gel was found to be dependent on applied feed pressure as well as bulk feed concentration.…”
Section: Specific Resistance Of Silica Gelmentioning
confidence: 87%
See 4 more Smart Citations
“…It appears that dependence of specific resistance on bulk feed concentration and applied pressure is due to the nature &the deposit and particle size distribution in suspension. Previous studies have suggested that specific resistance of silica gel depends on physiochemical properties of bulk solution and operating conditions [9][10][11][12]. The specific resistance of this gel was found to be dependent on applied feed pressure as well as bulk feed concentration.…”
Section: Specific Resistance Of Silica Gelmentioning
confidence: 87%
“…Several studies [9,10,12,17] in the past have reported the relationship of operating conditions and specific resistance of deposited layers. An influence of applied pressure and bulk feed concentration on the deposit was reported in all of these studies.…”
Section: Specific Resistance Of Silica Gelmentioning
confidence: 99%
See 3 more Smart Citations